STUDY OF NARRATION ON SATYA BUDHI TEMPLE’S GATE IN BANDUNG - Edbert Theo Fortino; Tessa Eka Darmayanti (Ide dan Dialog Desain Indonesia (Idealog), 2023)
This article examines narratives in architectural forms to details of the ornaments and reliefs onthe gate as one of the important components in a temple building because as it starts from the architectural form of the temple gate until the details of its ornaments and reliefs that engraved on its surface tells a story, meaning, and deep philosophy to its people. Satya Budhi Temple as one of the oldest temples in Bandungthat has been established for more than 15 decades, which is around 157 years until it is designated as a heritagebuilding type A becomes the object of research in this article as the temple building has a very high historical value. This study aims to narrate the meaning, story, and philosophy behind the architectural formof thegate to the details of its ornaments and reliefs that are engraved or drawn along the surface of the gate. Thisresearch method was carried out qualitatively using a case study approach with cultural and historical theory to study the components of architectural elements, to the meaning and story that is rooted throughthereliefs and decorative ornaments at the gate. There is also a research instrument which is observation, andinterview guidelines as the key instruments. The data source of this research is the result of interviews fromthe management of Satya Budhi Temple, Architects or researchers with specialization or expertiseinheritage buildings or building with cultural elements, as well as the surrounding community. So that thisresearch has an impact to find out the story and philosophical meaning that is implied through the formof Satya Budhi's temple gate components form. Keywords : Gate; Narration; Temple; Ornament; Philosophy